خلافت: قرآن و سنت اور اسلاف کے اقوال کی روشنی میں (Al-Qamar, 2024)
Caliphate is a term which is used in Islamic history for the governmental system adopted by companions of the prophet Muhammad (S.A.W) in the light of the teaching of Islam. Madina was the capital for caliphate. The system of appointment of the Caliph used to vary time to time. The model system of caliphate was finished with the death of 4th Caliph Hadrat Ali (R.A). There were found monarchy system in Banu Ummayad, Banu Abbas period, and later on in Ottoman Empire in Turkey but, they always used to name themselves Caliphs. Caliph was considered the sole leader of the all the Muslims living all over the world. Last living Ottoman Empire ended in 1923 after the World War 2. Now Muslims have no caliph, who can solidify them, that’s way they are diversified.  For the time being, there are groups among the Muslims who do not believe in Caliphate. They have doubts in this regard whether caliphate is proved by Quran and Sunnah or not? Some of them believe in democracy or other nature of dominion. I tried my best to prove caliphate in the light of Quran, Sunnah and sayings of the predecessors.
Keywords: Caliphate; Quran; Sunnah; Sayings of the Predecessors